A concise review on epigenetic regulation: insight into molecular mechanisms. - Golbabapour, S.; Abdulla, M.A.; Hajrezaei, M. (2011)
Epigenetic mechanisms are responsible for the regulation of transcription of imprinted genes and those that induce a totipotent state. Starting just after fertilization, DNA methylation pattern undergoes establishment, reestablishment and maintenance. These modifications are important for normal embryo and placental developments. Throughout life and passing to the next generation, epigenetic events establish, maintain, erase and reestablish. In the context of differentiated cell reprogramming, demethylation and activation of genes whose expressions contribute to the pluripotent state is the crux of the matter. In this review, firstly, regulatory epigenetic mechanisms related to somatic cell nuclear transfer (SCNT) reprogramming are discussed, followed by embryonic development, and placental epigenetic issues.